Transformación de la no-Complejidad a la Complejidad - Maldonado Castañeda, Carlos Eduardo (Ingeniería, 2016)
Context: This paper deals with a new and most difficult problem, namely the way in which a simple or linear system or phenomenon can be transformed into a complex or non-linear phenomenon or system thanks to the fractals geometry. In this sense, the framework is set out by the sciences of complexity. Such a problem is extremely important, for in general it has been said that complex science deals, among others, with non-linear behaviors. As a conclusion, the geometry of fractals provides bases solid enough to study the transformation herewith considered. The theoretical and practical meaning of the problem raised here can be extended to numerous fields. Here such a transformation is explored and shown for the first time. Method: The method here is theoretical. However, in the specialized bibliography the problem considered here has never been worked out, namely: whether, and if so how a simple or complicated system can be changed into a complex or non-linear one. Results: Working on the basis of fractal geometry the transformation from linear systems into non-linear is possible. Various arguments are shown that support an idea that sends back to G. Julia and Mandelbrot. Conclusions: As a conclusion, the geometry of fractals provides bases solid enough to study the transformation herewith considered. The theoretical and practical meaning of the problem raised here can be extended to numerous fields. Here such a transformation is explored and shown for the first time.